Moderate Attitude in Conflict Resolution Between Religions (Study of Tafsir Al-Azhar, An-Nur, and Al-Mishbah) - Fauzan, Ahmad; Ramadhan, Dian; P, Naura Nisrina; Habibi, M. Dani (JURNAL JAWI, 2022)
Indonesia is a unitary state with a heterogeneous population consisting of various ethnic groups, religions, races, and groups (SARA). Indonesian society with this diversity, has the potential to cause friction or conflict. Indonesian mujtahids who interpret the Qur'an offer conflict resolution efforts in their commentary books. This paper aims to explore the moderate attitude as an effort to resolve the Indonesian conflict in Tafsir Al-Azhar, An-Nur, and Al-Mishbah. This research is classified as library research with analytical descriptive nature. Treating everyone fairly and being tolerant of differences that are not related to faith and promoting peace are moderate attitudes offered by Indonesian commentators as an effort to resolve conflicts.